2019
DOI: 10.1080/13880209.2019.1618344
|View full text |Cite
|
Sign up to set email alerts
|

Phytotherapy in treatment of Parkinson’s disease: a review

Abstract: Context : Parkinson’s disease (PD) is a neurodegenerative disorder due to gradual loss of dopaminergic nerves in the substantia nigra (SN) in the midbrain. PD leads to certain motor disorders including resting tremor, muscle stiffness and slow movement. Medicinal plants have shown positive pharmacological effects in treating different models of PD. Objective: Tendency to use natural products, especially plants, for the treatment of PD has been growing. This article reviews th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…On the other hand, curcumin ( 12 ), a yellow pigment isolated from the rhizome of curcuma longa (turmeric), extensively used in traditional medicine for thousands of years, has been widely studied because of its uncountable therapeutic properties [ 39 ], from cancer [ 40 , 41 ] and arthritis [ 42 ] to neurodegenerative diseases [ 43 ] like Parkinson [ 44 ] and Alzheimer [ 45 ], as well as pain [ 46 ]. Its biological activity is mainly attributed to its particular chemical structure, having the advantage of low toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, curcumin ( 12 ), a yellow pigment isolated from the rhizome of curcuma longa (turmeric), extensively used in traditional medicine for thousands of years, has been widely studied because of its uncountable therapeutic properties [ 39 ], from cancer [ 40 , 41 ] and arthritis [ 42 ] to neurodegenerative diseases [ 43 ] like Parkinson [ 44 ] and Alzheimer [ 45 ], as well as pain [ 46 ]. Its biological activity is mainly attributed to its particular chemical structure, having the advantage of low toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant properties of gallic acid have been exploited in the solution of neurodegenerative disorders, such as Alzheimer's and Parkinson's diseases. [53][54][55] As shown in Table 3, a number of studies have demonstrated the protective effects of gallic acid on brain damage in different animal models.…”
Section: Degenerative Diseasementioning
confidence: 99%
“…Human SH-SY5Y neuroblastoma cells (ECACC Cat# 94030304, passages [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], grown in standard conditions, as already reported [14] were sub-cultured at 70-80% confluent, medium changed twice/week and experiments were performed by using cells in the exponential phase of growth.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Slice viability along with tissue edema were determined at the end of the treatments. The effects of PRES per se were assessed in slices treated with the extract (10-200 µg/mL) for a corresponding period (2 h) [12].…”
Section: Pres Treatmentmentioning
confidence: 99%
See 1 more Smart Citation